Analysis of Teenagers' Interests and Talents in Hadroh Music (Study on the Roudlotul Qulub Singaraja Indramayu Hadroh Group - Akhnaf Adilatul Fakhiroh (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study aims to analyze the interests and talents of adolescents in the art of hadroh music, specifically within the Roudlotul Qulub hadroh group in Indramayu. As a form of Islamic cultural expression, hadroh music plays an important role in the development of youth character, creativity, and identity. Using a qualitative case study approach, data were collected through interviews and direct observation of the group's members. The results indicate that hadroh serves as a positive medium for self-development, strengthening social bonds, and enhancing spiritual and moral values. Involvement in hadroh also positively impacts adolescents' social, cognitive, and emotional skills. Sustainable support is needed to ensure that hadroh continues to appeal to and be preserved by younger generations.